Uresničevanje usmerjenega izobraževanja na področju zdravstvene nege - Domajnko, Nana; Grbec, Vera; Kavalič, Stana (Obzornik zdravstvene nege, 1985)
In the past, educational programmes in nursing care were designed according to a medical model. They have been gradually modified, and today they focus on the activities and tasks characteristic of individual professions in the area of nursing. Nursing is an independent and indispensable component of health care: if forms its own theoretical models, starting points and methods, and is engaged in research in the field. Today’s specialised education covers general education and job-oriented training (undergraduate training programmes- Grade V, VI and VII programmes, specialisation programme), training in independent performance of various activities characteristic of the occupation (probation and job-oriented programmes) and education and continuing education. Groups of technical subjects, nursing process and various occupations within the area of nursing are presented. The principles observed in the nursing process stimulate progress in terms of methodology and organization, although the introduction ofthis process will undoubtedly pose many difficulties. Team work shoulď undergo many changes: nurses themselves should undertake full responsibility for future development of their profession. Grade VII programme, leading to the degree in nursing, is being worked out.